Faktor-Faktor yang Berhubungan dengan Kepatuhan Membayar Iuran pada Peserta BPJS Kesehatan Mandiri di Kota Jayapura - Lisnah Lisnah; Arifuddin Arifuddin; Mursalim Nohong (STIE AMKOP, 2023)
The implementation of National Health Coverage (JKN) mandates the compulsory enrollment of all Indonesian citizens as participants, thereby granting them access to essential healthcare services and protection. The rise in the number of individuals enrolled in the Jaminan Kesehatan Nasional (JKN) program in Jayapura does not correspond with the level of adherence among participants in fulfilling their contribution obligations. The objective of this study is to identify the parameters associated with compliance in paying contributions among independent participants of BPJS Kesehatan in Jayapura. The present study employed a quantitative research methodology, specifically utilizing an analytical survey approach within a cross-sectional design. The study sample consisted of individuals who were participants of the independent BPJS Kesehatan program. The sample method employed in this study was the use of an incidental sampling methodology, wherein a total of 245 independent individuals from BPJS Kesehatan in Jayapura were selected. The data were obtained through a research study, wherein participants' responses on the questionnaire were recorded as scores. The data underwent analysis through the application of hypothesis testing, which commenced with the utilization of the F test (ANOVA), t test, and Coefficient of Determination (R2) analysis. The findings indicate that there exist three key elements that impact the level of compliance regarding payment of contributions among independent BPJS Health members in Jayapura City. These characteristics are identified as knowledge, education, and motivation, accounting for a significant proportion of 78.3%. Hence, it is imperative for BPJS Kesehatan in Jayapura to enhance its outreach efforts in order to effectively communicate the significance of health insurance for the sustenance of the community, while also elucidating the advantages that may be derived from it.. Keywords: Obedience, Knowledge, Income, Motivation